(untitled) (Nexus International Journal of Science and Education, 2024)
The study investigated English language teachers' experiences with the adoption of artificial intelligence (AI) tools in the English language classroom. This study employed a phenomenological research design to determine the experiences and perceptions of the eight participants. The themes under the positive experiences of English teachers on adapting artificial intelligence (AI) tools in the teaching-learning process were assists in improving language skills and providing enhanced and immediate feedback. Meanwhile, the themes under negative experiences were poor academic integrity due to over reliance and reduced human interaction. Teachers coping with the challenges instilled academic integrity through citation and attribution, practicing critical framing, applying transformative learning, and providing authentic learning. Lastly, the educational management insight’s themes were finding the right AI tools for language learning, employing hybrid teaching strategies, and acquiring digital literacy skills. The themes suggest that balancing technological advancements with traditional pedagogical methods becomes imperative, indicating that teachers must embrace innovation while preserving the essential human touch in education. Moreover, the results generated provided comprehensive data for future research with similar scope. This study may be published in a reputable research journal.